A comparative study on the health and well-being of adolescent immigrants in Spain and Portugal - Hernando Gomez, Angel (2013)
The terms on which the integration of new generations of immigrants into Portuguese and Spanish societies happens will have a decisive influence in the future of both countries. Therefore, promoting their health, well-being, and psychosocial adaptation is a matter of strategic interest. This paper analyses psychosocial factors associated with well-being and psychological adjustment on a sample of 108 adolescents (55 males and 53 females), children of immigrants from Huelva (Spain) and Algarve (Portugal), aged between 10 and 17 years. Adolescents were assessed for demographic characteristics and perceived well-being. We used the “KIDSCREEN-5”, a self-report questionnaire that yields detailed profile information for children aged 8 to 18 years for the following ten dimensions: Physical well-being, Psychological well-being, Moods and emotions, Self-perception, Autonomy, Parental relationships and home life, Financial resources, Social support and peers, School environment, and Social acceptance(Bullying). Overall, significant differences were found between the Spanish and Portuguese samples on physical well-being, psychological well-being, mood, financial resources and social acceptance (bullying). Boys perceived themselves as having a better physical well-being than girls. Mothers’ educational level was associated with psychological well-being and mood. Also, results suggested that residence location and other socio-demographical variables were not associated with the adolescents’ well-being and psychological adjustment.